Neuraminidase inhibitors for preventing and treating influenza in children. - Matheson, N; Symmonds-Abrahams, M; Sheikh, A; Shepperd, S; Harnden, A (2003)
BACKGROUND: During epidemic years, influenza attack rates in children exceed 40%. Options for prevention and treatment include immunisation, amantadine and rimantadine, and the neuraminidase inhibitors: zanamivir and oseltamivir. OBJECTIVES: Our objective was to assess the efficacy, safety and tolerability of neuraminidase inhibitors in the treatment and prophylaxis of influenza infection in children. SEARCH STRATEGY: We searched the Cochrane Acute Respiratory Infections Group Specialised Trials Register, the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and the GlaxoSmithKline Clinical Trials Register, generally from inception through to December 2002. We also screened the references of retrieved articles and scrutinised relevant web sites. We also screened references of retrieved articles and other systematic reviews, scrutinised web sites of European and US regulatory bodies, and contacted manufacturers and authors. SELECTION CRITERIA: Double-blind randomised controlled trials comparing neuraminidase inhibitors with placebo or other antiviral drugs in children less than 12 years of age. Additional safety and tolerability data from other sources were also included. DATA COLLECTION AND ANALYSIS: Four reviewers applied the inclusion criteria to the retrieved studies, assessed trial quality and extracted data. Data were analysed separately for oseltamivir and zanamivir. MAIN RESULTS: We identified three randomised controlled trials reporting data from 1500 children with a clinical case definition of influenza, of whom 798 had laboratory confirmed influenza infection. Two were trials of oseltamivir (in healthy children and in children with asthma) and one was a trial of zanamivir (in healthy children). Overall, trial quality was good. Oseltamivir reduced the median duration of illness by 26% (36 hours) in previously healthy children with laboratory confirmed influenza (p < 0.0001) and by 17% (21 hours) in the intention-to-treat population (p = 0.0002). Zanamivir reduced the median duration of illness by 24% (1.25 days) in previously healthy children with laboratory confirmed influenza (p < 0.001) and by 10% (0.5 days) in the intention-to-treat population (p = 0.011). Both drugs also significantly reduced the time to return to normal activity. Only oseltamivir produced a significant reduction in the complications of influenza (particularly otitis media), although there was a trend to benefit for zanamivir. No data on the use of zanamivir in 'at risk' children were available. The reduction in time to resolution of illness in 'at risk' children (with asthma) treated with oseltamivir was not statistically significant. Although we identified three trials of neuraminidase inhibitors in the prevention of influenza in families (including children), Roche and GlaxoSmithKline were not willing to break-out data for paediatric populations, and so no data were eligible for inclusion in the review. The adverse events profile of zanamivir was no worse than placebo and we found no reports of zanamivir-induced bronchospasm in children. Vomiting was more common in children treated with oseltamivir (p = 0.008), but study withdrawals were similar (<2%) between oseltamivir and placebo. REVIEWER'S CONCLUSIONS: Neuraminidase inhibitors were effective in shortening illness duration and hastening return to normal activity in previously healthy children with a clinical or laboratory diagnosis of influenza. Oseltamivir was effective in reducing the incidence of secondary complications. Efficacy in 'at risk' children remains to be proven. The drugs are safe, but oseltamivir can cause vomiting.